2016
DOI: 10.31018/jans.v8i2.844
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and morphological studies on Ponnampet leaf and neck blast isolates of Magnaporthe grisea (Herbert) barr on rice (Oryza sativa L.)

Abstract: The study was carried out to standardize the optimal growth, sporulation and production of perfect stage of pathogen on different media. Among different media used such as Potato dextrose Agar (PDA), Oat meal Agar, Ragi flour agar, yeast extract + 2% soluble starch, Host extract + 2% soluble sucrose agar, Potato dextrose agar + Biotin + Thiamine and Rice flour agar, Oat meal agar and potato dextrose agar was found to be best media for radial growth and sporulation of M. grisea. Maximum conidia length (9.46μm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The effect of different media on the radial growth and colony description of Pyricularia oryzae is presented in Jagadeesh and Devaki (2020) [10] studied cultural morphology of 72 Magnaporthe oryzae isolates on OMA and PDA and observed significant growth. Teli et al (2016) [18] reported that PDA and OMA were found to be the best media for radial growth of Magnaporthe grisea isolated from Ponnampet. [21] recorded maximum growth and sporulation of the Bipolaris oryzae on corn meal agar medium followed by potato dextrose agar (PDA) and rice leaves agar.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of different media on the radial growth and colony description of Pyricularia oryzae is presented in Jagadeesh and Devaki (2020) [10] studied cultural morphology of 72 Magnaporthe oryzae isolates on OMA and PDA and observed significant growth. Teli et al (2016) [18] reported that PDA and OMA were found to be the best media for radial growth of Magnaporthe grisea isolated from Ponnampet. [21] recorded maximum growth and sporulation of the Bipolaris oryzae on corn meal agar medium followed by potato dextrose agar (PDA) and rice leaves agar.…”
Section: Resultsmentioning
confidence: 99%
“…The slants were allowed to incubate at 28 °C for 48 hours before being stored at 4 °C. The culture was refreshed every two months to maintain pure isolates of M. oryzae obtained through the hyphal tip isolation method (Al Noman and Shamsi, 2021;Teli et al, 2016).…”
Section: Monoconidial Isolationmentioning
confidence: 99%
“…A control group consisted of non-inoculated plants, while inoculated plants were protected with transparent nylon bags to maintain required air moisture, and symptoms' development was periodically monitored. Infected plants were subjected to re-isolation, and islate obtained were compared with the one used during inoculation for the confirmation of the pathogen identity (Hasan et al, 2016;Teli et al, 2016).…”
Section: Pathogenicity Testmentioning
confidence: 99%